The Dangers of Gullible Reading: Narrative as Seduction in García Márquez' Love in the Time of Cholera - M. Keith Booker (Studies in 20th & 21st Century Literature, 1993)
Gabriel García Márquez's Love in the Time of Cholera has frequently been read largely as a beautiful love story involving the lifelong fascination of Florentino Ariza with Fermina Daza and the eventual consummation of that fascination. Meanwhile, the text gains much of its energy from an opposition between the poetic romanticism of Ariza and the practical (though somewhat sinister) scientific thinking of Dr. Juvenal Urbino, Fermina's longtime husband. However, this opposition is not nearly as simple as it might appear, Ariza and Urbino being just as susceptible to the narrative of scientific progress as Ariza is to bad poetry, and Ariza being just as blind to the negative effects of his actions as is Urbino. Numerous elements of the text also militate against reading the book as a simple love story, though the text is clearly constructed to invite such readings. Love in the Time of Cholera invites, then undermines a number of reading strategies, thereby demonstrating the seductiveness of narrative in general and warning against gullibility in the reading of texts or of the world.
Keywords: seduction; Gabrial García Márquez; Love in the Time of Cholera; reading strategy; narrative; narrative strategy; gullibility; Colombian literature